Iowa Bird Life report for September 1 to November 30, 1976 - DeCoster, Richet al (1976)
Iowa Bird Life report contributed by Rich DeCoster, December 3, 1976. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Fall, 1976. Epson - sheet feed/flatbed